Evaluation of an Upper Cretaceous limestone from the area of Arta for lime production - CHRISTIDIS, G.; TRIANTAFYLLOU, G.; MARKOPOULOS, T. (Bulletin of the Geological Society of Greece, 2001)
Calcination of an Upper Cretaceous limestone from the Ionian Unit at 700-1100°C for 1-4 hours yielded very reactive lime end products. Lime formation was monitored by means of kinetic curves and TTT diagrams. Particle size seems to control the onset of lime crystallization at low temperatures, but is of minor importance at higher temperatures. With the experimental setting used, lime formation was completed at 900 °C. The specific surface area of the end products increases with firing temperature up to 800 °C, decreasing thereafter. Decrepitation of lime increases gradually with firing temperature. Hydration temperature during slaking increases rapidly up to 900 °C being relatively constant thereafter. Sintering and production of fines during firing control the physical properties of lime.